No place for truth, or, Whatever happened to evangelical theology? - Wells, David F (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 1993)
How are we to explain the fragmentation of evangelical faith today and the current turmoil in the churches? According to David Wells, the answer lies in seeing how modernity is reshaping the whole of Western culture, including that part of it which is religious. This book provides a compelling critique of the modern world and the state of evangelical theology
Wells's sweeping analysis explores the collapse of theology in the church, the academy, and modern culture. The new environment in which we live, with its huge cities, triumphant capitalism, invasive technology, and incessant amusements, is homogenizing daily experience, bringing about a world cliche culture. While the modern world has produced astonishing abundance, it has also taken a dreadful toll on the human spirit, emptying it of meaning, depth, and morality
Seeking respite from the acids of modernity, people today have increasingly turned to religions and therapies centered on the self. And, whether consciously or not, evangelicals have taken the same path, refashioning their faith into a religion of the self. Because the modern churchgoer is so often a consumer, pastors are redefining their roles in terms of their own marketability
Evangelicals, argues Wells, have largely lost the truth that God also stands outside all human experience, that he still summons sinners to repentance and belief regardless of their self-image, and that he calls his church to stand fast in his truth against the blandishments of the modern world
Written expressly to encourage renewal in evangelical theology, No Place for Truth explores the interface between Christian faith and the modern world in entirely new ways and with uncommon rigor. It raises profound questions about the future of conservative Protestant faith. Here is provocative reading for scholars, ministers, Christian leaders, seminary students, and all theologically concerned people
A delicious paradise lost -- World cliche culture -- Things fall apart -- Self-piety -- The rise of everyperson -- The new disablers -- The habits of God -- The reform of evangelicalism
Includes bibliographical references (pages 302-315) and index
Keywords: No Place For Truth; Evangelicalism -- United States -- History -- 20th century; Christianity and culture